2017
DOI: 10.4049/jimmunol.1601907
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Specific Expression of IL-37 in Hyperlipidemic Mice Attenuates Atherosclerosis

Abstract: Atherosclerosis, the progressive buildup of plaque within arterial blood vessels, can lead to fatal downstream events, such as heart attack or stroke. A key event contributing to the development of atherosclerosis is the infiltration of monocytes and its associated inflammation, as well as the formation of lipid-laden macrophage foam cells within the vessel wall. IL-37 is recognized as an important anti-inflammatory cytokine expressed especially by immune cells. This study was undertaken to elucidate the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…As shown in previous studies, IL-37-expressing cells exert protective effects on several established animal disease models [21,22]. Therefore, we examined whether IL-37-producing T-cells could improve the colitis activity in our DSS-induced mouse model.…”
Section: Resultsmentioning
confidence: 83%
“…As shown in previous studies, IL-37-expressing cells exert protective effects on several established animal disease models [21,22]. Therefore, we examined whether IL-37-producing T-cells could improve the colitis activity in our DSS-induced mouse model.…”
Section: Resultsmentioning
confidence: 83%
“…Recently, Li et al [ 31 ] reported that the IL-37 was highly expressed in the elderly T2DM patients, and that this expression correlated with the insulin resistance index, suggesting the association of this cytokine with insulin resistance and sensitivity. It has been reported that in vitro IL-37 expression reduces macrophage inflammation and migration and inhibits modified LDL uptake, suggesting an athero-protective role for macrophage-expressed IL-37 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…and LMC mice aged 12-17 weeks as described previously (57). For experiments involving MnCl 2 , portions of the macrophages were differentiated for 6 days and replated in the presence of 5 μM MnCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Human and mouse macrophage capacity to efflux uptaken radioactive cholesterol toward standardized HDL and ApoA-1 was performed as described previously (57,58).…”
Section: Detection Of Free and Esterified Cholesterol In Macrophagesmentioning
confidence: 99%